The Defiant Optimist Daring to Fight Global Inequality, Reinvent Finance, and Invest in Women. - Shahnaz, Durreen (1517 Media, 2023)
When she launched the world's first social stock exchange, Durreen Shahnaz started more than a financial system; she sparked a movement. Defiant optimism means changing how systems work--and who they work for. In these pages Shahnaz offers strategies for placing women, the underserved, and the planet at the heart of financial systems.